Platelet-Rich Plasma (PRP) in Breast Cancer Patients: An Application Analysis of 163 Sentinel Lymph Node Biopsies. (22nd October 2020) - Eichler, C.; Baucks, C.; Üner, J.; Pahmeyer, C.; Ratiu, D.; Gruettner, B.; Malter, W.; Warm, M.
Abstract : Introduction . Literature shows platelet-rich plasma (PRP) to improve overall outcomes in orthopedics, dermatology, ophthalmology, gynecology, and plastic surgery. Data on oncological patients is very limited. Only one publication is available on PRP in breast cancer patients. This work evaluated PRP in sentinel node biopsy procedures for breast cancer patients in terms of complication rates and oncological short-term follow-up. Methods . The evaluated PRP was ACP®, i.e., autologous conditioned plasma by Arthrex®. Between 2015 and 2018, 163 patients were offered to receive an ACP®/PRP injection in their lymph node biopsy site. Recruitment resulted in an approximate one-to-one ratio for analysis. Endpoints were major (revision) and minor (seroma, hematoma, and infection) complications rates as well as distant metastases, local recurrence, and overall survival. Median follow-up was 30 months. Results . Complication rates and oncological follow-up showed PRP to be applicable to use in a sentinel node biopsy scenario in breast cancer patients. There were 0 revisions in the ACP®/PRP group and 1.2% revisions in the control group (not significant). Oncological follow-up showed zero (0) distant metastases and local recurrences as well as a 100% 30-month overall survival. Conclusions . This is the first analysis of ACP®/PRP used in breast cancer patients in a sentinel node biopsy setting worldwide. PRP does not seem to increase rates of local recurrence within this 30-month follow-up time frame. Also, trend towards decreasing complication rates could be shown.